Cloud Networking: Implications of Agile virtualization on Provider Relationships - Aranda Gutierrez, Pedro; Carapinha, Jorge (Electronic Communications of the EASST, 2011)
SAIL is a Framework Programme 7 project that aims at providing scal- able and adaptive solutions to enhance the Internet Although not a formal con- tinuation of the 4WARD project, SAIL integrates many of the advanced concepts developed there. One of the focuses of the project, Cloud networking (CloNe), can be conceived as the successor of the Virtual Networks activities in 4WARD. This article concentrates on the initial discussions on the proposed model for Cloud networking (CloNe) and the implications it has for inter-provider relationships in the SAIL Framework.